23. EFFECTIVENESS OF SYNBIOTICS ON HEALTH STATUS OF CHILDREN FROM 24 TO 59 MONTHS OLD IN PHU LUONG DISTRICT, THAI NGUYEN PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate of the effectiveness of Synbiotics on health status of children aged 24-59 months in Phu Luong district, Thai Nguyen province.Subjects and methods: A community intervention study was conducted with 606 children meeting research criteria, randomly assigned in intervention and control group. The intervention group used a nutritional product containing Synbiotics for four months with the dose of two sachets per day.Results: During the four months of intervention, the number of episodes of acute upper respiratory tract infections, acute diarrhea, and functional constipation in the intervention group were 1.7 ± 2.2 episodes, 0.4 ± 1.2 episodes, and 1.4 ± 4.5 episodes, all significantly lower than those in the control group (p < 0.05 - Mann Whitney U test), with corresponding figures of 2.5 ± 3.1 episodes, 0.9 ± 2.2 episodes, and 2 ± 5.5 episodes.Conclusion: The intervention study using a nutritional product containing Synbiotics showed significant effects after four months of intervention. Children who consumed the product experienced a reduction in the number of episodes and the risk of acute upper respiratory tract infections, acute diarrhea, and functional constipation. Therefore, the product and the intervention method proposed in this study are appropriate to improve disease conditions in children aged 24 to 59 months.
Keywords: Disease; children 24-59 months old; Thai Nguyen province.